PENGARUH WAKTU ULTRASONIKASI TERHADAP KARAKTERISTIK TEPUNG JELAI (COIX LACRYMA-JOBI L) - Agustin, Sukmiyati; Nisa, Aulia (Jambura Journal of Food Technology, 2025)
Jelai (Coix lacryma-jobi L.) is a plant that produces seeds and can be consumed like cereals. The high carbohydrate content makes jelai suitable for processing into flour. Native jelai flour has the disadvantages of being susceptible to retrogradation and syneresis, not resistant to changes in pH, temperature, or mechanical treatment so that modifications need to be made to improve its characteristics, one of which is ultrasonication. This study aims to determine the effect of ultrasonication time on the physicochemical and functional characteristics of jelai flour. The results showed that ultrasonication time had a significant effect on colour analysis a* and b* of modified jelai flour and no significant effect on water absorption capacity, amylose content, and viscosity. The highest a* colour analysis value was obtained from the 60-minute ultrasonication time treatment of 2.05 and the highest b* value was obtained from the 50-minute ultrasonication time of 9.58. The increase in a* and b* values is due to the high heating temperature during ultrasonication time which can change the chemical composition of flour which affects the colour.